Distal tourniquet or leg position after injection enhances the efficacy of sciatic nerve blockade by the popliteal approach - (:unkn) unknown (My University, 2011)
Background: In this study, we hypothesized that leg positioning and distal tourniquet application, when compared with neutral positioning of the leg, alters the efficacy of sciatic nerve block performed by the double-stimulation technique. METHODS